The Federal Democratic Republic of Ethiopia : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that recent macroeconomic developments in The Federal Democratic Republic of Ethiopia are encouraging, with a significant deceleration in inflation and continued robust economic growth. Despite significant decline in coffee prices and supply bottlenecks, growth remains robust, supported by better agriculture output and construction and other services activities. Inflation declined from the peak of 40 percent in July 2011 to about 7 percent in June 2013. This has significantly eased the extent to which real interest rates were negative. Fiscal policy at the general government level remains prudent with cautious execution of the government budget.